Cartilage matrix-inspired biomimetic superlubricated nanospheres for treatment of osteoarthritis. (June 2020) - Chen, Hao; Sun, Tao; Yan, Yufei; Ji, Xiuling; Sun, Yulong; Zhao, Xin; Qi, Jin; Cui, Wenguo; Deng, Lianfu; Zhang, Hongyu
Abstract: The superlubrication of natural joint has been attributed to hydration lubrication of articular cartilage. Here, inspired by the structure of phosphatidylcholine lipid (a typical cartilage matrix) with the presence of zwitterionic charges, we developed superlubricated nanospheres, namely poly (2-methacryloyloxyethyl phosphorylcholine)-grafted mesoporous silica nanospheres (MSNs-NH2 @PMPC), via photopolymerization. The biomimetic nanospheres could enhance lubrication due to the formation of a tenacious hydration layer surrounding the zwitterionic charges of polymer brushes (PMPC), and achieve local delivery of an anti-inflammatory drug employing the nanocarriers (MSNs). The tribological and drug release tests showed improved lubrication and sustained drug release of the nanospheres. Additionally, the in vitro and in vivo tests revealed that the superlubricated drug-loaded nanospheres inhibited the development of osteoarthritis by up-regulating cartilage anabolic components and down-regulating catabolic proteases and pain-related gene. The nanospheres, with an integrated feature of both enhanced lubrication and sustained drug delivery, can be an efficient intra-articular nanomedicine for the treatment of osteoarthritis.